Application of water soluble chitosan for vannamei shrimp (Litopenaeus vannamei) preservation at chilling temperature - Harahap Serarifi Elagin; Kusdarwati Rahayu; Agustono (BIO Web of Conferences, 2024)
Active biomolecules such as chitosan and its derivatives have a role in food products preservation due to its antimicrobial properties. The aim of this study is to determine the ability of water soluble chitosan to extend shelf life of peeled and deveined shrimp stored at the chilling temperature. This study used completely randomized design using three treatments (control, 2% chitosan solution, and 2% water soluble chitosan solution) with six replications. Samples were tested for aerobic plate count, pH, total volatile base nitrogen, and sensory (appearance, odor, and texture). Experiments on water soluble chitosan indicated number of microbes was still within the safe limit until the 6th day. This could be identified from the number of microbes which still could be accepted by consumers (< 5 x 104 colonies/gram) at the 6th day, while in the control treatment the microbial amount within the safe limit until the 3rd day. Total Volatile Base Nitrogen of water soluble chitosan treatment was 3.69 mgN/100 grams. The pH value of shrimp treated with water soluble chitosan was 6.8, while in the organoleptic test, water soluble chitosan treatment had significant difference from control (P <0.05). This research conclude that water soluble chitosan have properties that can preserve food products specially vanamei shrimp.